MANAJEMEN PUSAT SUMBER BELAJAR BERSAMA (PSBB) PADA MADRASAH ALIYAH NEGERI (MAN) MODEL MANADO PROVINSI SULAWESI UTARA - Bolotio, Rivai (Universitas Papua, 2017)
This research was a field study that was intended to investigate on : 1) how the management of Common Lerning Resources Center (CLRC) at the Manado Model Public Islamic High School (hereafter MMPIHS) or Madrasah Aliyah Negeri (MAN) Model Manado was planned ? how the organization pattern of management of CLRC at MMPIHS was organized ? and 2) what were the inhibiting and supporting factors in implementing the management of CLRC at MMPIHS?A case study of qualitative approach was utilized in this study. Techniques used in collecting data were: Observation, interviews, and documentation. From the result of the data analysis, these following some conclusions were drawn: 1) the managerial functions covering planning, organizing, actuating, supervising and evaluating, were not yet implemented according to the principles of educational management; 2) supporting factors toward the managing of CLRC at MMPIHS such as: a) facilities (buildings/rooms, tools, equipments, books etc), b) qualified staff, c) conducive working environment, were available but not fully empowered; 3) the inhibiting factors toward the managing of CLRC at MAN Model Manado such as: a) the absence of Â managers with sufficient knowledge and skills who can manage and operate CLRC professionally, b) the insufficiency of funding to support the oprational activities for the management of CLRC, c) the lack of socialization of the existence of CLRC MMPIHS, d) the inavailability of operational vehicles for transportation in supporting the operational management of CLRC at MAN Model Manado. Up until now these inhibiting factors havenot yet been overcome with the result that they have decelerated the CLRC management process.